Bio-Efficiency of Compost Extracts on the Wet Rot Incidence, Morphological and Physiological Growth of Okra ( Abelmoschus Esculentus [ (L.) Moench ] ). - Siddiqui, Yasmeen; Meon, Sariah; Ismail, Razi; Rahmani, Mawardi; Ali, Asgar (2008)
An experimental was carried out of investigate the efficacy of rice straw and empty fruit bunch (EFB) of oil palm Compost Extracts either fortified or unfortified with Trichoderma harzianum on morphophysiological growth and occurrence of Choanephora wet rot oh okra. Treatments tested were water (control) (TI), rice straw (RST) compost extract (T2), Trichiderma-enriched RST compost extrast (T3), empty fruit bunch of oil palm compost extrast (T4), Trichiderma-enriched EFB compost extract (T5), AQUEOUS SUSPENSION OF Trichoderma (T6), and a fungicide Dithane M-45® (2 g -1 of water) (T7). The experimental results revealed significant variations amongst the treatment in respect of morphological characters e.g. shoot length, tap root length, number of leaves per plant, leaf area. The shoot and tap root length, number of leaves per plant, leaf area were significantly (P ≤ 0.05) higher in Trichoderma-enriched RST compost extracts (T3( followed by Dithane M-45® (T7), Trichiderma-enriched EFB extracts (T5), RST (T2), EFB (T4) and aqueous suspension of T. harzianum (T6) in both Choanephora inoculated and uninoculated (control) plots. Similarly, net photosynthetic rate and chlorophyll content were higher in plants receiving Trichiderma-enriched RST compost extracts (T3) with 76.2% reduction in Choanephora wet not incidence when compared with rest of the treatment. These experimental result revealed that morpho-physiological characters of okra could be modified by the application of Trichiderma-enriched compost extract would be more beneficial in environmentally friendly okra cultivation and may be used as an alternative to inorganic fertilizers/fungicides to enhance plant growth and reduce disease incidence subsequently, resulting in higher yield.